Variation in the coloration pattern of Anablepsoides hartii (Cyprinodontiformes: Cynolebiidae) in coastal streams of Venezuela - Infante-Rivero, Edwin (Revista de Biología Tropical, 2018)
Anablepsoides hartii is a non-annual fish of the family Cynolebiidae. Historically, this species has presented some inconsistencies for proper identification, due to a variation in the color pattern. The aim of this study was to describe and illustrate the different types of color patterns found in this species. For this purpose, we examined a total of 336 preserved specimens (19 lots) deposited in the ichthyological collections of the Museo de Biologia de la Universidad Central de Venezuela and the Museo de Ciencias Naturales in Guanare, Venezuela. The specimens were sorted by distinctive characteristics of size, sex and locality. Besides, we took photographs of each individual, vectorized them with detail, separating light and dark colorations and delimited color patterns of the same tone with the program Corel Draw version x7 (Spanish). My analysis showed that A. hartii presented four colors patterns. The color morphs were classified as: 1 male, 2 female, 3 intermediate and 4 montane. The first two color morphs were separated by sexual characters (sexual dimorphism); in turn, the intermediate color morph presented characters of both males and females in the same individual. Finally, the montane color morph differed from the previous ones by presenting a series of incomplete lateral rows, followed by a half-body reticulation to the tail. This analysis allowed the identification of the differences in this morphologically variable species.